The usage of psychometric equations in processing of master and doctoral theses in the Sudanese universities in the Khartoum – the capital, during (2015- 2020) - Abdalla, Abdalla Mohamed; Ahmed, Omar Ibrahim (Journal of Educational and Psychological Sciences, 2022)
This paper aimed to identify the use of psychometric equations (PE) in masters and doctoral theses that were defended at universities in Khartoum from (2015- 2020). The sample consisted of (n = 692) dissertations (Masters = 320, PhD = 372). The researchers used descriptive survey method, and designed a survey form. The researchers reached the following results: Order of use of PE: Cronbach’s alpha (α), Split- half coefficient, and factor analysis. There were differences in the use of PE according to the academic degree variable. There were differences in the use of PE in Masters according to the universities variable. The researchers put forward a number of recommendations including: The need to diversify the statistical indicators used in the interpretation of research results.